PENGARUH UKURAN PERUSAHAAN, STRATEGI, DAN BUDAYA TERHADAP KINERJA KEBERLANJUTAN (STUDI EMPIRIK PADA KELOMPOK INDUSTRI BAHAN BAKU DAN KIMIA DASAR YANG TERDAFTAR DI BEI TAHUN 2020-2024) - Azzahra, Novia; Fisher, Bobby (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This research was conducted to determine the influence of resource factors such as company size which has indicators of number of assets, number of subsidiaries and number of business segments, strategy which has indicators of expansion as well as operational and capital efficiency, as well as culture with indicators of customer orientation, innovation and employee orientation on sustainability performance. The population used was 203 companies consisting of all raw materials and basic chemical industrial companies in the 2020-2024 period registered on the IDX. The sample was selected based on the purposive sampling method so that 26 companies were obtained with 5 years of research from 2020 to 2024, and a total of 130 observation data were obtained. The method used was multiple linear regression analysis using Eviews 13. The results of the analysis showed that the company size variable, namely the number of assets, subsidiaries and business segments had a significant positive effect on sustainability performance. The strategy variable shows that expansion strategy and operational efficiency strategy have an insignificant negative effect on sustainability performance, while capital efficiency strategy has a significant negative effect on sustainability performance. The culture variable shows that customer-oriented culture has an insignificant positive effect on sustainability performance, while innovation culture has an insignificant negative effect on sustainability performance, and employee-oriented culture has a significant negative effect on sustainability performance.